Pengaruh Pertumbuhan Penduduk, Kesempatan Kerja Terhadap Pengangguran dan Kemiskinan di Kabupaten Aceh Utara - Chairunnisa Chairunnisa; Muliana Padang; Mahdiyyah Azra; M Azrul Azwar; Asnidar Asnidar; Ahmad Ridha (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to analyze the effect of population growth, employment opportunities on unemployment and poverty in North Aceh district. this study uses secondary data obtained from the Central Statistics Agency (BPS). with the period 2013-2022 in North Aceh District. This research model is path analysis using the eviews application. Based on the results of research that has been conducted on the Effect of Population Growth and Employment Opportunities on Unemployment and Poverty in North Aceh Regency, it shows that population growth has a negative and significant effect on unemployment, employment opportunities have a positive and insignificant effect on unemployment, population growth has a positive and insignificant effect on poverty, employment opportunities have a negative and significant effect on poverty and indirectly population growth has a significant effect on poverty through unemployment and also indirectly population growth has an insignificant effect on poverty through unemployment.